Gender and globalization in Asia and the Pacific : method, practice, theory - Ferguson, Kathy E.; Mironesco, Monique (University of Hawaii Press, 2008)
"What is globalization? How is it gendered? How does it work in Asia and the Pacific? The authors of the sixteen original and innovative essays presented here take fresh stock of globalization's complexities. They pursue critical feminist inquiry about women, gender, and sexualities and produce original insights into changing life patterns in Asian and Pacific Island societies. Each essay puts the lives and struggles of women at the center of its examination while weaving examples of global circuits in Asian and Pacific societies into a world frame of analysis. The work is generated from within Asian and Pacific spaces, bringing to the fore local voices and claims to knowledge. The geographic emphasis on Asia/Pacific highlights the complexity of globalizing practices among specific people whose dilemmas come alive on these pages. Although the book focuses on global, gendered flows, it expands its investigation to include the media and the arts, intellectual resources, activist agendas, and individual life stories. First-rate ethnographies and interviews reach beyond generalizations and bring Pacific and Asian women and men alive in their struggles against globalization."--Book cover